2003
DOI: 10.1242/jeb.00252
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin modulates the electric waveform of the gymnotiform electric fishBrachyhypopomus pinnicaudatus

Abstract: The gymnotiform electric fish Brachyhypopomus pinnicaudatus communicates with a sexually dimorphic electric waveform, the electric organ discharge (EOD). Males display pronounced circadian rhythms in the amplitude and duration of their EODs. Changes in the social environment influence the magnitudes of these circadian rhythms and also produce more transient responses in the EOD waveforms. Here we show that injections of serotonin produce quick, transient, dosedependent enhancements of the male EOD characters s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
99
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(103 citation statements)
references
References 34 publications
3
99
0
Order By: Relevance
“…High 5-HT turnover in parts of the brain has been found in aggressive and dominant individuals (Korzan et al, 2000;Matter et al, 1998) and a "primed" serotonergic system may be necessary to enable an individual to produce an appropriate behavioral response in a complex social context (Sperry et al, 2005). These findings would help explain the apparent paradox we observed in our fish wherein 5-HT injections further masculinized the males' EODs (Stoddard et al, 2003). If the classical account of the serotonin system as an inhibitor of aggression is accurate and enhancements of the EOD in the presence of conspecifics are aggressive, then the reduction in EOD parameters following activation of the 5HT 1A R makes perfect sense, but the increase in these parameters following activation of the 5HT 2 R is unexpected.…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…High 5-HT turnover in parts of the brain has been found in aggressive and dominant individuals (Korzan et al, 2000;Matter et al, 1998) and a "primed" serotonergic system may be necessary to enable an individual to produce an appropriate behavioral response in a complex social context (Sperry et al, 2005). These findings would help explain the apparent paradox we observed in our fish wherein 5-HT injections further masculinized the males' EODs (Stoddard et al, 2003). If the classical account of the serotonin system as an inhibitor of aggression is accurate and enhancements of the EOD in the presence of conspecifics are aggressive, then the reduction in EOD parameters following activation of the 5HT 1A R makes perfect sense, but the increase in these parameters following activation of the 5HT 2 R is unexpected.…”
mentioning
confidence: 55%
“…Social encounters and environmental stimuli modulate the EOD waveform by altering the membrane biophysics and discharge waveforms of individual electrocytes (Ferrari et al, 1995;McAnelly and Zakon, 2000;Mills and Zakon, 1991), resulting in either a larger or smaller waveform. Social encounters modulate the EOD within minutes and large waveforms and/or rapid enhancements are associated with dominance status (Franchina et al, 2001;Hagedorn and Zelick, 1989;Stoddard et al, 2003).We have shown that intramuscular injections of 5-HT cause male B. pinnicaudatus to increase their EOD amplitude and duration akin to the waveform changes observed during male-male social interactions (Stoddard et al, 2003). These effects of 5-HT do not result from its direct action on the electrocytes, whereas melanocortin peptides do modulate the discharge waveforms of single electrocytes directly (Markham and Stoddard, 2005).…”
mentioning
confidence: 87%
See 3 more Smart Citations